ANALISIS PENGARUH EFEKTIVITAS, EFESIENSI, DAN TRANSPARANSI ALOKASI ANGGARAN PENDAPATAN DAN BELANJA DESA TERHADAP KINERJA PEMERINTAH DESA DI KECAMATAN POLANHARJO - Agustin Sri Lestari; Rukmini Rukmini; Wikan Budi Utami (Jurnal Ilmiah Manajemen dan Akuntansi, 2024)
The purpose of this study is to determine the influence of the effectiveness, efficiency, and transparency of the allocation of the Village Revenue and Expenditure Budget on the Performance of the Village Government in Polanharjo District. The methodology used in this study is a quantitative data analysis method and the test is carried out with a multiple regression model. The population used in this study is 131 village apparatus in Polanharjo District. In this study, a sample of 61 respondents was obtained. With a significance value of 0.001 less than α = 0.05, this shows that the effectiveness variable has a significant effect on the performance of the Village Government. The significance value of 0.000 is less than α = 0.05, which shows that the efficiency variable has a significant effect on the performance of the Village Government. With a significance of 0.001 smaller than α = 0.05, this shows that the transparency variable has a significant effect on Village Government Performance. Based on the results of the Fcal data test of 74.442 is greater than the Ftable of 2.76 with a significance of 0.000 less than the significance value of     α = 0.05, so it can be concluded that simultaneously or together the variables of effectiveness, efficiency, and transparency are factors that affect the variables of Village Government Performance.